Potensi Curcumin dan 4 Herbal Empon-Empon Dalam Memodulasi Kekebalan Sel T Terhadap Covid-19 - Aryo Tedjo; Dimas Noor; Rudi Heryanto (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Longer immunity to Severe Acute Respiratory Syndrome-CoronaVirus-2 (SARS-CoV-2) infection is thought to occur through memory cellular responses by activity of specific T lymphocytes. However, most patients with Coronavirus disease-19 (Covid-19) experienced a decrease in the number of T lymphocytes or lymphopenia. Agents that help maintain T cell counts such as Curcumin appear to have played an important role during the Covid-19 pandemic. Curcumin is known to provide a balance between T cell effectiveness and T cell autoaggressiveness, as well as restoring memory T cell function as observed in tumor-induced mice. The mixture of 4 herbal extracts of empon-empon which is commonly used as herbal medicine, namely temulawak, ginger, lemongrass, and turmeric, is thought to have the same effect as curcumin. This is known from the tracing of a plant-protein-compound database which shows that there are not many compounds other than curcumin that can modulate T cells. It is necessary to study the role of Curcumin and a mixture of 4 herbal empon-empon in modulating T cells in cases of infection by the SARS-Cov-2 antigen.